Implementation of Waste Management Policy in Jatikalang Village, Krian District, Sidoarjo Regency - Emalia Putri Agustin; Hendra Sukmana (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The purpose of this study was to analyze the waste management carried out by TPST Jatikalang Village, Krian District. The approach taken in this study is a descriptive qualitative approach, by conducting interviews, documentation, and observations. The data analysis model uses the analysis model according to Miles and Huberman (1994), with data collection techniques, data reduction, data presentation and drawing conclusions. The results of this study indicate that first, communication in the implementation of TPST management policies in Jatikalang Village where the Village Government has increased communication efforts that are more interactive, consistent and clear, and involve active community participation. Second, the resources in managing TPST are lacking in the number of workers needed so that a lot of rubbish accumulates in people's homes and there is also a lack of enthusiasm for TPST workers who often pick up the rubbish during the day even though they should be able to pick up rubbish from people's homes from 7 o'clock. Third, the attitude and disposition of policy implementers with positive responses and support from policy implementers, the appointment of appropriate bureaucracy, and the provision of appropriate incentives are the main keys in ensuring that waste management policies can run effectively. Fourth, the bureaucratic structure in implementing the TPST management policy in Jatikalang Village where the SOP at the Jatikalang Village TPST is in accordance